KEMAMPUAN KOMUNIKASI INTERPERSONAL GURU AGAMA KRISTEN DALAM MEMBENTUK PERILAKU KRISTIANI SISWA - Safatulus Giawa; Resti Damai Yanti Zai; Gulo, Sadile Asrani; Hulu, Aperius El Putra; Gulo, Deti Rosmeidar (STT Ekklesia Pontianak, 2024)
Abstract: Christian religious teachers in the learning process often ignore interpersonal communication in shaping students' Christian behavior through Christian religious education. This happens because Christian religious teachers only focus on information or messages through knowledge understood by students and focus on explaining learning materials and learning material targets. The purpose of this study was to determine how the interpersonal communication skills possessed by Christian religious education teachers in shaping students' Christian behavior. This study uses a literature study research method, with the implementation steps being first; collecting literature related to the research. Second; selecting and selecting valid and renewable sources. Third; conducting source analysis and fourth; presenting the results of data analysis. Based on the results of data analysis and presentation, it was found that interpersonal communication of Christian religious teachers needs to be carried out actively and routinely, because interpersonal communication is a means to convey messages appropriately, therefore Christian religious teachers need to create safe learning for students in shaping students' Christian behavior. Abstrak: Guru agama Kristen dalam proses pembelajaran sering mengabaikan komunikasi interpersonal dalam membentuk perilaku kristiani siswa melalui pendidikan agama Kristen. Hal ini terjadi karena guru agama Kristen hanya fokus pada informasi atau pesan melalui pengetahuan yang dipahami oleh siswa dan fokus pada penjelasan materi pembelajaran serta target materi pembelajaran. Tujuan penelitian ini dilakukan untuk mengetahui bagaimana kemampuan komunikasi interpersonal yang dimiliki oleh guru pendidikan agama Kristen dalam membentuk perilaku kristiani siswa. Penelitian ini menggunakan metode penelitian studi pustaka, dengan langkah-langkah pelaksanaannya adalah pertama; mengumpulkan literatur yang berkaitan dengan penelitian. Kedua; memilih dan menyeleksi sumber yang valid dan terbarukan. Ketiga; melakukan analisis sumber dan keempat; menyajikan hasil analisis data. Berdasarkan hasil analisis dan penyajian data, maka ditemukan bahwa komunikasi interpersonal guru agama Kristen perlu dilakukan secara aktif dan rutin, karena komunikasi interpersonal merupakan sarana untuk menyampaikan pesan secara tepat, oleh karena itu guru agama Kristen perlu menciptakan pembelajaran yang aman bagi peserta didik dalam membentuk perilaku kristiani siswa.